PENGEMBANGAN LKPD PEMBELAJARAN IPAS BERBASIS CONTEXTUAL TEACHING LEARNING UNTUK KELAS V MADRASAH IBTIDAIYAH - Nailis Sa’adah; A. Jauhar Fuad (Abtadi : Jurnal Pendidikan Dasar, 2025)
ABSTRACT This study aims to develop Contextual Teaching Learning (CTL)-based StudentWorksheets (LKPD) for Science and Social Studies (IPAS) on natural phenomena topics for fifthgrade Islamic Elementary School (MI) students. Using the ADDIE model (Analyze, Design,Development, Implementation, Evaluation) within a Research and Development (R&D) approach,the study involved 11 fifth-grade students at MI Miftahus Sa'adah Ngawi. Data were collectedthrough expert validation (content, design) and practitioner assessments, along with studentresponse questionnaires. The Results of developed LKPD met validity criteria with scores of: (1)86.6% from content experts, (2) 90% from design experts, and (3) 94.2% from practitioners (all"highly valid"). Product attractiveness scored 86.5% among students ("highly attractive"),particularly in visual appeal (92%). The LKPD effectively integrated seven CTL principles,especially in connecting materials to students' real-life contexts. This research provides acontextual teaching material development model aligned with the Merdeka Curriculum, serving asa reference for meaningful IPAS instruction. Future research should expand testing with largersamples and develop LKPD variants for other IPAS topic